Comparison of Quantitative Descriptive Analysis to the Napping methodology with and without product training. Issue 3 (30th April 2018) - Oliver, Penelope; Cicerale, Sara; Pang, Edwin; Keast, Russell
Abstract: Napping has recently been gaining popularity as a rapid descriptive profiling method, primarily for the reduction in cost and time when compared with traditional descriptive analysis. Questions remain regarding the accuracy of data from untrained consumers and how this differs from a trained panel. The aim of this research is to compare results obtained from a Quantitative Descriptive Analysis (QDA) strawberry‐trained panel with untrained consumers applying Napping combined with ultra‐flash profile (UFP). Six strawberry samples (three duplicate cultivars) were assessed. Untrained consumers ( n  = 131) used Napping to separate strawberries based on their similarities and differences. Trained panelists ( n  = 12, minimum 60 hr training), applied QDA and Napping on two separate occasions. Results revealed Napping with UFP to produce product configurations comparable to QDA (RV coefficients of 0.936 and 0.898 between QDA and Napping via a trained panel, and a consumer panel, respectively), with similar descriptive terms to describe products. With a reduction in the number of consumers applying Napping with UFP, however, the similarity between methodologies declined. Furthermore, a lack of common understanding of attribute definitions limited its application. Therefore, Napping with UFP applied by a larger pool of assessors has been deemed an appropriate alternative to QDA when time is limited. Practical application: The comparison of the Napping with ultra‐flash profile (UFP) methodology to traditional descriptive analysis will provide insight into consumer perception, and how this differs from an expertly trained panel. Upon evaluating this technique, Napping with UFP using untrained consumers may prove to be a valid instrument in objectively profiling the flavor of non‐homogenous agricultural products, potentially proving a viable alternative to the traditional QDA methods in future research of these products.